Synthesis, mechanism studies of rhodium complexes and electrochemical oxidation, spectroscopic properties of phenol derivatives - Chen, Shan Shan (2011)
A series of rare five-coordinate organorhodium(III) intermediates [Rh(N^C)(PAr3)2CH=CHR]PF6 (N^C = benzo[h,f]quinoline, benzo[h]quinoline, 2-phenylpyridine, R = para-Ph-(SO2CF3, CF3, NO2, Cl, F, H, CH3, OCH3), CH2Ph, CH2CH2Ph, Ar = para-Ph-(OCH3, CH3, F)) and subsequent C–C coupling rhodium(I) complexes [Rh(N^C–CH=CHR)(PAr3)2]PF6 have been isolated and fully characterized. The total mechanism of C–H activation and subsequent C–C reductive elimination from the rhodium center has been proposed and the electronic effects of reactive ligands CH=CHAr and ancillary ligands PAr3 on the rate of the C–C reductive elimination reactions from the five-coordinate intermediates were studied. The absolute rate of C–C reductive elimination has been measured and the rate decrease as the vinyl ligands with more electron-withdrawing groups and the ancillary ligands PAr3 with more electron-donating groups. We also measured the kinetics in different solvents like CD2Cl2, THF-d8 and acetone-d6 in order to probe the impact of the solvent’s polarity and donating ability on the rate of the reaction. The result shows that the coordinated solvent can accelerate the rate of reductive elimination step. Chelation-assisted activation of C–X bonds (X = Cl, Br, and I) took place in the reaction of [Rh(PPh3)2(acetone)2]PF6 and 2-(2-halophenyl)pyridine or 10-halobenzo[h]quinoline. A series of 16-electron five-coordinate cationic rhodium(III) monohalide complexes was synthesized at room temperature. Neutral octahedral rhodium(III) dihalide complexes were obtained when the corresponding cationic monohalide complexes were further heated in acetone. Rhodium and iridium diiodides with these cyclometalation motifs could be alternatively synthesized from the reaction of the corresponding cyclometalated hydride complexes and I2. X-ray crystal structures of representative monohalide and dihalide complexes are reported. Octahedral rhodium(III) dihalide complexes are active catalysts for the dimerization of terminal alkynes, while 16-electron cationic rhodium(III) monohalides are inactive.